Pemberdayaan Masyarakat dalam Mitigasi Bencana Menuju Desa Siaga di Desa Pancarejo Semanu Gunung Kidul Yogyakarta - Wirawati, Maulidta Karunianingtyas; Aini, Dwi Nur; Prasetyorini, Heny; Prihati, Dyah Restuning; Wahyuningsih, Wahyuningsih; Pramono, Wijanarko Heru; Prasetiya, Chandra Hadi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Pancarejo Village, Semanu, Gunung Kidul, is an area with high disaster vulnerability. This training aims to empower the community with basic knowledge and skills in disaster management, thereby reducing the risk of loss of life and material loss, which is the first step in realizing a Disaster Preparedness Village. The objectives of this community service activity include providing the community with a comprehensive understanding of the types of disasters that may occur and training them in appropriate emergency measures, such as self-evacuation, first aid, and the use of safety equipment. A total of 25 participants participated in this activity, consisting of village officials and disaster preparedness cadres. After the training, understanding increased from 58.4% to 87.2%. The community service activities conducted demonstrated that community-based emergency response training can be an effective strategy in increasing community disaster preparedness.